Assessment of post-exposure anti-rabies therapy in goats - Raji James (Department of Veterinary Epidemology and Preventive Medicine, College of Veterinary and Animal Science, 2005)
The effectiveness of post-exposure therapy against rabies in goats, with two different vaccines viz., inactivated tissue culture anti-rabies vaccine (Raksharab®) and DNA combined tissue culture anti-rabies vaccine (Dinarab®), was studied with different schedule of vaccination, in Thrissur, Kerala. The rabies virus neutralizing antibody titres were assessed by using rapid fluorescent focus inhibition test (RFFIT). Sixty unvaccinated goats exposed to rabid animal bite were selected for study. Group I animals were given inactivated tissue culture anti-rabies vaccine and group II animals were given DNA combined tissue culture anti-rabies vaccine in schedule I (“Essen”). Group III and group IV were treated with inactivated tissue culture anti-rabies vaccine and DNA combined tissue culture anti-rabies vaccine in schedule II whose five injections were given on 0, 1, 2, 3 and 4th day. By day 14, all animals in-group I had achieved rabies antibody titre above the protective level recommended by WHO (>0.5 IU/ml) and reached peak titre on day 28. Group II animals that received DNA combined tissue culture anti-rabies vaccine elicited protective titre on day seven and reached peak titre on day 28. All the goats in group I and group II were maintaining the protective titre till 90th day and none had developed rabies for a period of 180 days. Though both vaccines in schedule I (“Essen”) produced geometric mean rabies virus neutralizing antibody titre above 0.5 IU/ml up to 90th day of study period, DNA combined tissue culture anti-rabies vaccine induced earlier and higher virus neutralizing antibody titre. Both vaccines under schedule II produced good protection on seventh day. Inactivated tissue culture anti-rabies vaccine under schedule II elicited earlier and higher neutralizing antibody response than schedule I. Out of two vaccines used, DNA combined tissue culture anti-rabies vaccine induced higher geometric mean rabies virus neutralizing antibody titre in a rapid manner in both schedules. Animals were monitored monthly for six months after exposure and all treated groups were alive and no vaccine related serious adverse events occurred. It is concluded that DNA combined tissue culture anti-rabies vaccine in schedule I and schedule II or inactivated tissue culture anti-rabies vaccine in schedule II were observed as the best for recommending to the field for post-exposure anti-rabies therapy in goats.